2021
DOI: 10.4081/ija.2021.1872
|View full text |Cite
|
Sign up to set email alerts
|

Predictive phytotoxic value of water-soluble allelochemicals in plant extracts for choosing a cover crop or mulch for specific weed control

Abstract: Cover crops and mulches have become an alternative for soil management in vineyards due to the agronomic, environmental, and economic advantages, especially the possibility of weed control. Implicitly to this objective lies the idea of assessing the potential herbicide effect of the allelochemicals released by different cover crop and mulch species. With this objective, the present work evaluated the phytotoxic effects of 12 aqueous extracts of selected species with potential use as a cover crop or mulch: a Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Species included Bromus hordeaceus, B. rubens , Festuca arundinacea , Hordeum murinum , H. vulgare , Vulpia ciliata , Medicago rugosa , M. sativa , Trifolium subterraneum , T. incarnatum , Phacelia tanacetifolia , Sinapis alba , and Pinus sylvestris on three weed species Conyza bonariensis , Aster squamatus , and Bassia scoparia . Their results showed differential effects of the extracts in the suppression of the three weed species and concluded that aqueous extracts of some of these species demonstrated that they had potential to be used as cover crops for weed suppression [ 88 ].…”
Section: Mechanisms Of Weed Suppression By Cover Cropsmentioning
confidence: 99%
“…Species included Bromus hordeaceus, B. rubens , Festuca arundinacea , Hordeum murinum , H. vulgare , Vulpia ciliata , Medicago rugosa , M. sativa , Trifolium subterraneum , T. incarnatum , Phacelia tanacetifolia , Sinapis alba , and Pinus sylvestris on three weed species Conyza bonariensis , Aster squamatus , and Bassia scoparia . Their results showed differential effects of the extracts in the suppression of the three weed species and concluded that aqueous extracts of some of these species demonstrated that they had potential to be used as cover crops for weed suppression [ 88 ].…”
Section: Mechanisms Of Weed Suppression By Cover Cropsmentioning
confidence: 99%
“…Besides, weeds that manage to survive and produce seeds within the cover crop, have to face the mulching effect caused by the mowed residues of the cover crop. These residues act as a physical barrier and can also release allelochemicals (Lemessa & Wakjira, 2015; Puig et al, 2021), which can impair further growth and prevent weed germination. Despite this, the weed suppression capability of cover crops is highly dependent on the characteristics of both the selected cover crop and the target weed species (Baraibar et al, 2017; Lemessa & Wakjira, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate cover crop species for weed control needs to be selected based on its growth rate or leaf area development, time of establishment, self‐seeding capacity, amount of potential biomass produced, competitive ability or allelopathic potential (Ibáñez, 2015; Lemessa & Wakjira, 2015; Puig et al, 2021). Also, in water limited vineyards, like those in semiarid Mediterranean climates, cover crop species must be carefully chosen to prevent competition with vines; usually, those with short life cycle are chosen (Sullivan, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under natural environmental conditions, allelopathy occurs when chemicals produced by plants are released onto neighboring plants in the same population, affecting their germination, development, reproduction, and survival. Various allelopathic compounds, extracted from numerous different plant species, have already been tested for potential use in weed control within organic agricultural systems, and many of them have demonstrated destructive effects on some weed plants, inhibiting their seed germination and shoot and root elongation and disrupting their photosynthesis and water/nutrient uptake (Grisi et al, 2015;Jang et al, 2018;Puig et al, 2021). As the half-lives of natural compounds with allelopathic capacities are usually short-lived, there would be no concerns regarding residues in soil.…”
Section: Introductionmentioning
confidence: 99%